The role of tax treatment in promoting foreign investment - احمد, زكريا يونس (Journal of Legal Sciences, 2019)
The tax system in Iraq plays a prominent role in the process of attracting foreign investments to operate the money in the investment market of our country, through the incentives provided by the legal texts that stimulate foreign investors and pay to contract, and those incentives are the tax exemptions and tax obtained by the foreign investor, The Iraqi turned to that issue in the Iraqi investment law currently in force and amended, but we will try to shed light in this study on the extent of those incentives compared to what is granted by the comparative legislation? Is it enough that the legal texts brought by the Iraqi legislator to encourage foreign investor and reassurance of his money through investment in commercial projects within the country? So we tried to show the positive relationship between tax incentives on the one hand and foreign investment on the other hand.